Managerial economics in a global economy - Salvatore, Dominick (Oxford University Press, 2015)
"Reflecting the highly globalized nature of tastes, production, labor markets, and financial markets in today's world, Managerial Economics in a Global Economy, Eighth Edition, presents the theory of the firm as a unifying theme to examine the managerial decision-making process. Adopting a global perspective, it synthesizes economic theory, decision science, and business administration studies, examining how they interact as a firm strives to reach optimal profitability and efficiency in the face of modern constraints. Features * Integrates examples, data, and theories on the international ramifications of managerial decisions into the entire text, rather than segregating the material in a separate chapter * Incorporates 127 case studies, showing how firms actually reach managerial decisions today * Offers instructors maximum flexibility with a modular structure that is suitable for both full-term and briefer courses, and can be used with or without calculus * Includes a robust instructor ancillary package for adopters"--Provided by publisher.